2006
DOI: 10.1111/j.1365-2141.2006.06246.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet mass has prognostic value in patients with myelodysplastic syndromes

Abstract: Platelet mass (mean platelet volume x platelet count) can be derived from data obtained from the routine full blood count and separates patients with myelodysplastic syndromes (MDS) at diagnosis into three distinct prognostic groups: low platelet mass group - median survival 5 months and 5-year survival 0%; intermediate platelet mass group - median survival 30 months and 5-year survival 34%; high platelet mass group median survival - not reached at 82 months follow-up with a 5-year survival of 82%. These data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 9 publications
0
21
1
Order By: Relevance
“…Bowles et al. suggested that a low platelet mass is associated with shorter survival (13). As previously reported, platelet volume does not seem to influence the risk of bleeding at the time of diagnosis or the risk of fatal haemorrhagic complications (14).…”
Section: Discussionmentioning
confidence: 99%
“…Bowles et al. suggested that a low platelet mass is associated with shorter survival (13). As previously reported, platelet volume does not seem to influence the risk of bleeding at the time of diagnosis or the risk of fatal haemorrhagic complications (14).…”
Section: Discussionmentioning
confidence: 99%
“…A number of other features have been associated or correlated with prognosis in MDS, including BM microenvironment alterations (78-80), mean corpuscular volume (81), platelet mass (82), absolute lymphocyte count (83), basophilia and eosinophilia (84), hypoalbuminemia (85), and T-regulatory cells (86). A separate risk model for hypocellular MDS has also been proposed (87).…”
Section: Current Mds Prognostic Scoring Systems and Risk Modelsmentioning
confidence: 99%
“…For example, we could not examine survival in relation to previous chemotherapy treatment due to the unavailability of this information in the SEER Limited-Use Data. Furthermore, there are several factors that have been shown to predict survival in MDS which are not available in these data, such as cytogenetic abnormalities [4,6,31], blast counts [4,6,31], number of dysplastic lineages [4,6], and blood cell counts [6,32]. The International Prognostic Scoring System (IPSS) divides patients into four distinct groups based on percentage of bone marrow blasts, cytogenetic abnormalities, and number of peripheral blood cytopenias [6].…”
Section: Years)mentioning
confidence: 99%